Application of NDVI Transformation on Sentinel 2A Imagery for mapping mangrove conditions in Makassar City - Ahmad Faizal; Nita Mutmainna; Muh Anshar Amran; Amran Saru; Khairul Amri; Muh Nastsir Nessa (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
Mangrove ecosystems consist of tropical plants that have adapted to the salinity, tidal fluctuations, and loose soil condition. Identification of mangrove ecosystems can be carried out by direct survey methods or by utilizing remote sensing technology. This study aims to map the area, percent cover, and density of mangroves in Makassar City using Sentinel 2A Imagery. The method used is the NDVI transformation, followed by Unsupervised-ISODATA classification, ground check with the 10 x 10-meter plotting method, and hemispherical photography. The results showed that the existence of mangroves in Makassar City was still found in the Tallo and Biringkanaya districts, with 68.81 ha of mangrove ecosystem cover area in the range of 84.36 - 91.89% (dense category). Likewise, the vegetation index based on NDVI analysis ranged from 0.73 - 0.81 (dense category), and the species density was in the range of 2700 - 6400 trees/Ha (dense category). Sentinel-2A imagery transformed with NDVI can be used to track mangrove areas and their density. The wide distribution of mangrove ecosystems in Makassar is relatively small but has good conditions.